The Impact of Self-Directed Learning on Student Motivation and Creativity in Electronics Education: A Correlational Study - Riki Wahyudi; Sartika Anori; Hendra Hidayat; Dedy Irfan; Erik Pezo; Xiaohan Feng (Sagamedia Teknologi Nusantara, 2024)
The implementation of 21st-century education demands significant shifts in learning approaches, particularly in vocational high schools, where practical skills and creativity are paramount. This study investigates the impact of the Self-Directed Learning (SDL) model on students' motivation and creativity in the subject of electronic circuit applications at SMK Negeri 1 Batipuh. Using a descriptive correlational research design, data were collected from 34 students through validated and reliable questionnaires. The findings reveal that SDL contributes 46.9% to enhancing learning motivation and 39.69% to fostering creativity, indicating its significant influence on both variables. SDL empowers students to take greater control of their learning processes, thereby promoting intrinsic motivation and creative problem-solving abilities. These results align with previous research emphasizing the role of independent learning in improving academic performance and preparing students for the demands of the workforce. The practical implications of this study highlight the importance of optimizing SDL implementation in vocational education, particularly in technical subjects, to develop students' independence and creativity—skills essential for success in the digital era and professional environments. This study contributes to the advancement of effective learning models in vocational education, offering valuable insights for educators and policymakers to enhance the quality of teaching and learning.